Physicochemical and Sensory Properties of Coconut Flour Cake - Kamarul Azam, Khairin Najwa; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
The demand for healthier and functional baked goods has led to the exploration of alternative flours with higher nutritional benefits. This study investigates the potential of coconut flour as an innovative ingredient in butter cake formulations, focusing on its impact on physicochemical and sensory properties. Coconut flour, valued for its high dietary fiber content (60.9%), unique flavour, and ability to enhance the nutritional profile of baked goods, was evaluated in formulations with 10%, 20%, and 30% coconut flour substitutions alongside wheat flour. Physicochemical analyses revealed that increasing coconut flour content influenced moisture retention, texture, color, and pH, with higher substitution levels resulting in denser structures and distinct browning effects during baking. For example, the pH decreased from 8.30 (control) to 7.78 (30% substitution), and firmness increased from 344.88 g (control) to 393.2 g (20% substitution). Sensory evaluations conducted with 50 panelists highlighted that cakes containing 10% and 20% coconut flour achieved the best balance of appearance (7.58), flavor (7.58), texture (7.22), and overall acceptability (7.62), significantly outperforming the control. These findings demonstrate that coconut flour can elevate the nutritional value and sensory appeal of cakes without compromising consumer satisfaction. This study is timely, given the rising popularity of functional foods and consumer interest in natural ingredients that contribute to well-being. By addressing the technical challenges of incorporating coconut flour, this research offers valuable insights for food technologists and product developers aiming to create healthier, innovative bakery products that align with current food trends. Future studies should explore shelf-life stability and formulation optimization for large-scale bakery applications.